MITOS DALAM CERITA BALLAK TUJUA MASYARAKAT SUKU MAKASSAR DI ONTO BANTAENG SULAWESI SELATAN - Syuhada, Ummu Nurul; Hajrah, Hajrah; AJ, Andi Agussalim (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze the myth in the Ballak Tujua story in Onto Village, Bantaeng Regency using Levi-Strauss's structuralism theory. The research design used was descriptive qualitative. The data in that (1) Internal structure suggests that the seven leaders performed austerities to determine the king and provide guidance, so that Tumanurung is a figure of light who descends from the sky and provides guidance. A figure was found in Sulu Cinranaya and he was appointed king from among the seven leaders. There was the Akkawaru 12 Rajab traditional party and the Appakatinja event in Ballak Tujua. People's belief in the history of Ballak Tujua (2) The external structure seen from history is in line with the internal structure that Ballak Tujua in Onto Village is a leader who performs austerities to determine who will be king, so Tumanurung provides guidance. Belief in the Ballak Tujua myth has an influence on social life, people's beliefs have an influence on belief in myths and are influenced by the belief factor that everything will lead to good and avoid all evil.The data collection techniques used were field studies and documentation. This research focuses on the myth of the Ballak Tujua story in Onto Bantaeng. The research results showed that there were 19 data obtained from community interviews which included history and beliefs in the Ballak Tujua myth